ACADEMIC BURNOUT: DO COLLEGE STUDENTS WHO JOIN ORGANIZATIONS EXPERIENCE IT? - Octaviani, Mutiara Tri; Yandri, Hengki; Juliawati, Dosi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
The education system in universities puts much pressure on students so that they can meet academic requirements. This strict learning system can cause students to experience academic burnout, which impacts mental and academic health. This study aims to reveal academic burnout in students who join organizations and how many students experience academic burnout when participating in organizations. The research method used was quantitative, with a descriptive approach and a sample of 50 students participating in the organization. The measuring tool used is the Oldenburg Burnout Inventory – Student Version, which consists of 16 statements covering two dimensions, namely exhaustion and disengagement. The results revealed that an average of 36 students experienced academic burnout, or as much as 72%, and students who joined organizations experienced academic burnout. It recommended that further researchers research on a larger scale to get a complete picture of academic burnout experienced by students who join organizations.